Implementation of the Lex Certa Principle towards the Ambiguity of Digital Law's in Indonesia - Haritjahjono, Budi; Sodikin, Sodikin (Amnesti: Jurnal Hukum, 2025)
Ambiguity in Indonesia's digital laws, particularly in the Electronic Information and Transactions Law (ITE’s Law), has raised concerns over the criminalization of free expression and the erosion of digital rights. Vague terms like "contents against propriety" and "inflicting hatred or dissension" in Articles 27 and Article 28 often lead to subjective interpretations, undermining legal certainty and exposing individuals to unfair prosecution. This study examines the role of the lex certa principle in addressing ambiguities within ITE’s Law and its application to safeguard digital rights. Employing a normative legal research method, that analyzes and systematizes legal norms, synthesizes doctrines, and provides prescriptive justifications aligned with existing laws to guide legal decision-making. This study examines relevant provisions, judicial precedents, and international best practices, including regulatory frameworks in Canada, the European Union, and the United States. The findings highlight that Indonesia's digital laws lack clarity, making them prone to misuse and inconsistent enforcement. Key cases, such as Prita Mulyasari and Baiq Nuril, illustrate the detrimental impact of ambiguous regulations on individuals' rights. The study proposes reforming ITE’s Law by redefining ambiguous terms, enhancing law enforcement training, and adopting proportionality tests to ensure restrictions on expression are justified and lawful. By incorporating lex certa into digital regulations, Indonesia can balance public order and freedom of expression while protecting digital rights. The study concludes with recommendations for multi-stakeholder collaboration in regulatory reforms to create a fair and inclusive digital legal framework.